The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0080-62342011000600030
|View full text |Cite
|
Sign up to set email alerts
|

Revisão sistemática e metanálise sobre o valor preditivo da proteína C-reativa em infecção pós-operatória

Abstract: Português / Inglês www.scielo.br/reeusp RESUMORevisão sistemáti ca sobre a proteína C--reati va (PCR) a fi m de identi fi car seu valor prediti vo no prognósti co/diagnósti co de infecção em pacientes cirúrgicos. As fontes de busca foram: COCHRANE, EMBASE, LILACS, MEDLINE E OVID, e referências bibliográfi cas dos estudos encontrados. Em todos os estudos a elevação dos níveis de PCR foi observada após a cirurgia e na presença de infecções pós-operatórias (PO), em oito estudos um pico de PCR entre o segundo e o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…It is a sensitive but non-specific inflammatory biomarker often used as an indicator for systemic inflammatory response syndrome (SIRS) [1], [2] secondary to surgery or early postoperative complications [3]. However, its role as predictor for clinical deterioration in the surgical critically ill patient in the intensive care unit (ICU) remains unspecific.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a sensitive but non-specific inflammatory biomarker often used as an indicator for systemic inflammatory response syndrome (SIRS) [1], [2] secondary to surgery or early postoperative complications [3]. However, its role as predictor for clinical deterioration in the surgical critically ill patient in the intensive care unit (ICU) remains unspecific.…”
Section: Introductionmentioning
confidence: 99%
“…Studies about the value of CRP in the critically ill patient on the ICU are contradictory. Increased CRP concentrations in a heterogeneous population on the ICU have been associated with organ failure, prolonged ICU stay, high infection rates and mortality rates [3], [5], [6]. On the contrary, a recent review on the predictive value of CRP concentrations for survival concluded that CRP is not a good predictor for survival in the critically ill patient during the early course.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obese patients may present high CRP values ​​due to the chronic inflammatory condition developed by the increase of interleukin-6 and tumor necrosis factor in adipocytes, promoting the production of C-reactive protein by hepatocytes, inducing a state of chronic inflammation 3 , 14 , 23 . Due to the PCR/adipocyte ratio, it has been speculated that weight loss may decrease the chronic inflammatory state 21 . Increased inflammatory markers have been the focus of many studies, with emphasis on adipose tissue in obese patients as a causal factor of cardiovascular events 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Por se tratar de uma proteína não específica para infecção, uma metanálise conclui que utilização de proteína-C-reativa deve ser acompanhada de exames clínicos, o que não exclui seu valor como preditor de infecções (96). Em ensaio randomizado comparando ambos, não houve significativa diferença na redução de terapia antimicrobiana, mas a procalcitonina foi superior em reduzir os dias de terapia antimicrobiana e é demonstrado também em alguns estudos seu potencial em reduzir mortalidade (97) (98).…”
Section: Os Recursos Laboratoriais Dos Hospitais Avaliadosunclassified